Mapping Research Trends of Entropy-Based Weighting and AHP Integration in Multi-Criteria Decision Analysis for Sustainable Development Applications - Zulfikar Zulfikar; Juni Ismail; Alfry Aristo Jansen Sinlae; Yanto Saputra; Raja Anan Nasution; Elsy Rahajeng; Mesran Mesran (Graha Mitra Edukasi, 2025)
The integration of entropy-based weighting and the Analytic Hierarchy Process (AHP) has become an increasingly important strategy for balancing objective and subjective criterion weights in multi-criteria decision-making (MCDM), yet the intellectual structure of this hybrid field remains fragmented and insufficiently mapped. This study aims to systematically chart the global research landscape of entropy-AHP integration in MCDM and to identify its leading contributors, foundational works, and dominant thematic structures. A bibliometric research design guided by the PRISMA protocol was adopted, drawing on 160 English-language documents retrieved from the Scopus database for the period 2001 to 2025. The data were analysed using VOSviewer and Scopus analytical tools to examine annual publication trends, subject-area distribution, leading sources, co-citation networks, and keyword co-occurrence patterns. The results reveal a field that has accelerated sharply since 2021, reaching a peak of thirty-four documents in 2025, with output concentrated in Engineering and Computer Science and disseminated through a diverse ecosystem of energy-oriented journals and conference outlets. Co-citation analysis confirms a theoretical base anchored in the canonical works of Saaty and Zeleny, while keyword mapping shows entropy functioning as a conceptual bridge between expert judgment and data-driven weighting, with TOPSIS emerging as a salient companion technique. The novelty of this study lies in its focused mapping of the entropy–AHP intersection rather than MCDM in general, exposing a loosely integrated thematic structure and a reliance on a narrow citation canon. Its principal contribution is a consolidated knowledge map that clarifies the field's foundations and directs future methodological and interdisciplinary innovation.